2003
DOI: 10.1080/0735648x.2003.9721182
|View full text |Cite
|
Sign up to set email alerts
|

Prime-Time Crime: Presentations of Crime and Its Participants on Popular Television Justice Programs

Abstract: Television 's long fascination with crime makes a study of contempora y justice shows imperative. An analysis of three contempora yprime-timejustice shows (Law and Order, The Practice and NYPD Blue) was undertaken to discover the way in which crime and its particQants are presented by entertainment television. The findings revealed an overrepresentation of violent crime and distorted images of offenders and victims. These findings not only confirm research findings from previous studies ofprime-time crime show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 19 publications
0
21
0
1
Order By: Relevance
“…Entertainment television has recently become fascinated with violence and murder (Soulliere, 2003). Many new fictional and documentary shows have appeared in the past years.…”
Section: The Role Of the Media And Female Killersmentioning
confidence: 99%
See 1 more Smart Citation
“…Entertainment television has recently become fascinated with violence and murder (Soulliere, 2003). Many new fictional and documentary shows have appeared in the past years.…”
Section: The Role Of the Media And Female Killersmentioning
confidence: 99%
“…As a result our ideas and views are shaped based on the limited information the society wishes to provide us with" (Soulliere, 2003, para.3). Additionally, there is some evidence that the crimes presented and the manner of their portrayal through television shows are frequently inaccurate and distorted, which can in return influence the society's view over those crimes and cause false beliefs as well as distorted views about the crimes, the offenders, as well as the victims (Soulliere, 2003).…”
Section: The Role Of the Media And Female Killersmentioning
confidence: 99%
“…Nonetheless, a large body of research has found some support for a general relationship between greater exposure to media presentations of crime and both a public fear of crime and an overestimation of the prevalence of crime (Barille, 1984;Bryant, Carveth, & Brown, 1981;Gilliam & Lynegar, 2000;Gross & Aday, 2003;Hawkins & Pingree, 1982;Shanahan & Morgan, 1999;Weaver & Wakshlag, 1986). Other streams of research indicate that the media plays a more active role in the construction of social phenomena in situations where alternative information sources are either less available or direct experience is lacking (Gunter, 1987;Soulliere, 2003;Surette, 2007). This is especially true for crime, since the average person most likely has little direct experience with crime or the criminal justice system (Surette, 2007).…”
mentioning
confidence: 94%
“…Rafter, 2006) or television crime procedurals (Surette, 2007). Given research that indicates that the media plays an active role in the construction of social phenomena, particularly in situations where alternative information sources are either less available or non-existent (Soulliere, 2003;Surette 2007), there is a need to examine the portrayals of crime and justice in film.…”
mentioning
confidence: 99%
“…The first is that the portrayal of crime and offending is similar across programs. In particular, content analyses of TV crime dramas consistently find that • • the crimes shown are violent, and typically murder (Brown, 2001;Cavender & Deutsch, 2007;Deutsch & Cavender, 2008;Eschholz, Mallard, & Flynn, 2004;Rhineberger-Dunn, Rader, & Williams, 2008;Soulliere, 2003); • • offenders tend to be White (Britto, Hughes, Saltzman, & Stroh, 2007;Eschholz et al, 2004;Rhineberger-Dunn et al, 2008) and middle or upper class (Brown, 2001;Eschholz et al, 2004;Reiner, 2006;Rhineberger-Dunn et al, 2008;Soulliere, 2003); • • the explanations for offending lean toward the personal (e.g., psychopathy, greed, revenge) rather than the sociological (e.g., poverty, gangs; Rhineberger-Dunn et al, 2008;Soulliere, 2003); and • • the criminal justice system is portrayed as highly efficacious with respect to solving crimes (Britto et al, 2007;Dominick, 1973;Eschholz et al, 2004).…”
Section: Good Guys Wear Bluementioning
confidence: 99%